Good environmental governance for renewable energies: The example of Germany - lessons for China? - Mischa Bechberger; Danyel Reiche (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
Germany's pioneering role in the field of renewable energies (RES) can best be observed by its world leading position in installed wind power and photovoltaics. Also its first European rank in the production of biofuels and installed solar thermal collector space is remarkable. These successes are not due to an exceptionally good natural resource base; mainly they are the result of an innovative national support policy. Pressure from the European and international commitments also have contributed to the German success story in RES. The current paper analyses the main factors of the German case in the development of RES, including the design elements of the national promotion instruments and support programmes, the policy impacts from the European and the international level, technical as well as cognitive conditions. In addition, a description is given of further driving forces for a successful RES development in other European countries. The paper ends with the question which of the described success factors of the German RES case might be transferable to China - and which not.
Keywords: 300; Internationale Umweltpolitik; Deutschland; China